Teaching English: The Challenges Teachers Face and the Various Instructional Techniques - Zanyar Ghafar (RADINKA JAYA UTAMA PUBLISHER, 2023)
Although teaching is a great career, there are moments when it may be challenging. Due to the adoption of new teaching techniques and the extent to which electronic and intelligent training have permeated the area of education, the responsibilities of instructors have changed dramatically over time. This study aims, there are two primary areas of discussion on the challenges that teachers of young language learners encounter and the various instructional techniques that they may use. The resources and teaching methods now in use may be used to address the difficulties connected with teaching English. How well instructors can use the available materials for teaching English is the major topic of the study. According to the findings of this study, young pupils were getting Instruction in English as a second language utilizing an extensive range of digital tools. To provide the right teaching, tutors must be aware of each student's evolving requirements. Furthermore, it seems sense that the educational process might be stressful given the potential for issues. In order to prevent obstacles from impeding learning, each challenge should be constantly monitored by an experienced instructor.